PERAN HUBUNGAN MASYARAKAT DAN MANAJEMEN KEUANGAN DALAM PENGELOLAAN LEMBAGA PENDIDIKAN ISLAM - Pradinata, Yanuar Eka; Febrianti, Vika Chafidatun; Ramadhani, Zalva Okta; Rozaq, Akhmad Abdul; Mardiyah (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2026)
Financial management and public relations are two strategic aspects that support the sustainability of Islamic educational institutions. This study aims to examine the concept of financial management, the role of public relations, as well as the challenges and strategic efforts in managing Islamic educational institutions. This research employs a qualitative approach using a library research design with content analysis techniques on relevant literature sources. The findings show that effective financial management must be based on Islamic principles such as transparency, accountability, and justice, while public relations plays an important role in building a positive institutional image and public trust. The major challenges include limited human resource competencies, suboptimal financial management systems, and the demands of adapting to information technology and social media developments. This study highlights the novelty that the integration of financial management and public relations is essential for improving the quality and sustainability of Islamic educational institutions in the modern era